A photonumeric scale for the assessment of atrophic facial photodamage3. (30th March 2018) - Ayer, J.; Ahmed, A.; Duncan‐Parry, E.; Beck, P.; Griffiths, T.W.; Watson, R.E.B.; Griffiths, C.E.M.
Summary: Background: Photonumeric scales have consistently shown superiority over descriptive equivalents. They have the advantage of providing a consistent visual frame of reference by minimizing variability in perception and subjectivity. A photonumeric scale to assess hypertrophic facial photodamage already exists. However, there is currently no objective measure for atrophic facial photodamage. To address this, we have devised a nine‐point photonumeric standardized scale. Objectives: To design, test and validate a photonumeric scale for the assessment of atrophic facial photodamage against a descriptive scale for the same indication. Methods: A pool of 393 facial photographs ( en face and 45° oblique) from 131 individuals with atrophic facial photodamage was created. Five photographic standards were selected and assigned grades zero through to eight, where zero is no photodamage and eight is severe atrophic photodamage, thus making a nine‐point scale. Twenty photographs spanning the entire range of values were selected to test the scale. Testing was performed alongside a descriptive equivalent. A panel of 10 dermatologists, 10 nondermatology clinicians and 14 dermatology scientists marked the two scales; marking was repeated 1 week later. Results: There was a significantly greater agreement between the graders using the photonumeric scale than the descriptive scale (kappa values 0·71 and 0·37 with standardized errors of 0·57 and 0·17, respectively) with no significant difference in repeatability between the two methods ( P < 0·05). Conclusions: The study describes a new photonumeric scale for atrophic photodamage. This would be a useful adjunct in both the clinical and research settings. Abstract : What's already known about this topic? Photonumeric scales demonstrate consistent superiority when compared with descriptive equivalents. Hypertrophic facial photodamage has been assessed successfully in terms of both severity and treatment response using a well‐established photonumeric scale. What does this study add? A new photonumeric scale created and validated for the assessment of a newly recognized clinical phenotype of facial photodamage – atrophic photodamage. Linked Comment:  Li et al. Br J Dermatol 2018;178 :1008–1009 . Plain language summary available online Respond to this article